The Gending “Gorompol” in the Sundanese Wayang Golek Purwa Performance: Analysis of Structure and Function - Maulana, Marsel Ridky; Tresnadi, Soni; Narawati, Tati; Budiman, Agus; Suwandi, Miranto (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2025)
Gorompol is one of the sekar-gending repertoires that plays a significant role in Sundanese wayang golek purwa performances, particularly in the scenes of cabut kayon/gunungan, ibingan wayang, and murwa dalang. This study aims to examine the role, structure, and musical complexity of Gorompol within the context of wayang golek performances. The research employs content analysis with data collected through direct observation, audio-visual documentation, and interviews with both puppeteers (dalang) and musicians (wiyaga). The findings reveal that Gorompol is a distinctive piece commonly performed during daytime performances, characterized by a concise yet intricate musical structure. Its complexity is reflected in the flexibility of combining salendro and madenda laras systems during the murwa scene, the dynamic interaction among the puppeteer, musicians, singers (sinden), and vocal exclamations (alok), as well as the tightly regulated structural patterns despite its function as accompanying music. These findings highlight that Gorompol is not merely background music but a medium of expression that enhances the dramaturgy of the performance. The relevance of this study to contemporary performing arts lies in how Gorompol exemplifies collective creativity in preserving traditional continuity while simultaneously opening pathways for musical innovation in modern performance practices.